A 0.5-V 9.3-ENOB 68-nW 10-kS/s SAR ADC in 0.18-μm CMOS for biomedical applications. (January 2017) - Bai, Wenbin; Zhu, Zhangming
Abstract: This paper presents a 10-bit ultra-low power successive approximation register (SAR) analog-to-digital converter (ADC) intended for use in wearable biomedical circuits. In order to achieve the nanowatt range power consumption, an energy-efficiency modified VCM -based switching scheme is proposed. In addition, a fully dynamic comparator and a dynamic register are used to eliminate the static power consumption. To improve the signal linearity in such a low supply voltage, a double-boost bootstrapped switch is proposed. A prototype of the proposed SAR ADC was fabricated in 0.18 µm 1P6M CMOS technology within a bio-sensor front-end circuit, which occupies an active area of 370×390 µm 2 . The SAR ADC achieves 57.8 dB SNDR and consumes 68nW at 0.5 V supply voltage and 10 kHz sampling rate, resulting in a figure-of-merits (FOM) of 10.8fJ/conversion-step.